-3+(5z+9)=(7z+5)-6

Simple and best practice solution for -3+(5z+9)=(7z+5)-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3+(5z+9)=(7z+5)-6 equation:


Simplifying
-3 + (5z + 9) = (7z + 5) + -6

Reorder the terms:
-3 + (9 + 5z) = (7z + 5) + -6

Remove parenthesis around (9 + 5z)
-3 + 9 + 5z = (7z + 5) + -6

Combine like terms: -3 + 9 = 6
6 + 5z = (7z + 5) + -6

Reorder the terms:
6 + 5z = (5 + 7z) + -6

Remove parenthesis around (5 + 7z)
6 + 5z = 5 + 7z + -6

Reorder the terms:
6 + 5z = 5 + -6 + 7z

Combine like terms: 5 + -6 = -1
6 + 5z = -1 + 7z

Solving
6 + 5z = -1 + 7z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-7z' to each side of the equation.
6 + 5z + -7z = -1 + 7z + -7z

Combine like terms: 5z + -7z = -2z
6 + -2z = -1 + 7z + -7z

Combine like terms: 7z + -7z = 0
6 + -2z = -1 + 0
6 + -2z = -1

Add '-6' to each side of the equation.
6 + -6 + -2z = -1 + -6

Combine like terms: 6 + -6 = 0
0 + -2z = -1 + -6
-2z = -1 + -6

Combine like terms: -1 + -6 = -7
-2z = -7

Divide each side by '-2'.
z = 3.5

Simplifying
z = 3.5

See similar equations:

| 12x^2-8xy-20y^2= | | -0.8z+3.3=0.9 | | -6-6+20x=5(4x-5)+13 | | -0.8a+3.3=9.9 | | -3x-10=-4 | | 3a=9a+24 | | 6g^2+13gc+6c^2= | | -2t-1=3t-16 | | 3z-13=-10 | | 4x-2y=-12 | | -2+6=4v-6v | | 42m^2-29mn-5n^2= | | 9x+-2=4x+9 | | 0=8x+39 | | Y-2.8=2.2 | | Y-2.8=2.3 | | 15+8k=-34 | | 2x+3-x=6 | | 7y^2-4y-6= | | 6x+-1=x+13 | | s+2.5=6.25 | | 6(2X-4)=-32 | | -38=5x-x+10 | | 3x+(x+2)=20 | | 10x+-1=8x+6 | | 3x+9-x+4-2x=18 | | 9-24u+16u^2= | | 5x+-1=2x+11 | | 81-18s-3s^2= | | 7(x+3)-2(3x+1)=25 | | y^2+64=0 | | 38-30v=32 |

Equations solver categories